Comparative study of the pattern of tuberculosis in Suez and Damietta Chest Hospitals in the period 2007-2016 - Fares Mohammed Oaf; Ezzat Atwa Risk; Abd El Monem El-Shabrawi Metwally; Kamel Abd-Elghafar Elghonemy; Mokhles Abdel Fadil Zineldin; Abdel-Fatah Ahmed (Wolters Kluwer Medknow Publications, 2018)
Background Tuberculosis (TB) is an infectious disease affecting the world population for thousands of years. Aim The aim was to study and compare the pattern of TB in Suez and Damietta Chest Hospitals through the period from 2007 to 2016. Patients and methods This is a retrospective study that was carried out at Damietta and Suez Chest Hospitals and dispensaries and included all cases of TB from January 2007 to December 2016. Data were collected from TB registration units. Direct observed therapies strategy in chest hospitals and dispensaries started since January 1999. Results A total of 1208 (62.3%) cases were men and 732 (37.7%) were women. The highest rate of infection was reported in age group of 20-29 years (45.7%); the lowest affected age group was that greater than 60 years (5.1%). Type of TB was pulmonary in 76.1% and extrapulmonary in 23.9%. The main presenting symptom was cough presented in 50.8%, hemoptysis in 20.3%, chest pain in 14.7%, and fever in 14.2%. The sputum smear was positive in 89.3% and negative in 10.7%; and there was significant increase of positive smear in Damietta when compared with Suez Governorates (92.1 vs. 86.2%, respectively). The most common extrapulmonary lesion was pleural effusion (40.5%); then lymph node (19.4%) and the least was cold abscess (2.6%). Diabetes was reported in 11.5% and prolonged corticosteroid therapy in 6.5%. The condition at discharge was improvement in 85.5%, failure in 6.6%, relapse in 4.8%, and death in 3.1%. Both groups were comparable as regards the studied variables. Conclusion There was progressive decrease of total TB cases in both Damietta and Suez Governorate from 2007 to 2016 and both governorates were comparable.